Analysis of the Preparedness of Aircraft Rescue and Fire Fighting Officers in Overcoming Accidents and Fires at Adi Soemarmo Boyolali MAN Airport - Ricky Elvando Hutapea; Ika Fathin Resti Martanti (CV. Rayyan Dwi Bharata, 2023)
Every airport must have an Aircraft Rescue And Fire Fighting Unit (ARFF) or flight accident assistance and fire fighting. In supporting flight safety, the level of preparedness of the ARFF Unit must be high or required to always be on alert for incidents or incidents in the airport area so that the level of accidents, security and fires at the airport will be lower. The aim of this research is. to find out the preparedness of ARFF officers in the event of an accident and fire incident at Adi Soemarmo Boyolali airport and to find out the obstacles faced by Aircraft Rescue And Fighting (ARFF) Unit Officers in the event of an accident and fire at Adi Soemarmo Boyolali International Airport. This study used qualitative research methods. The research was carried out from 1 October 2022 to 30 November 2022 and continued with observation activities from 1 March 2023 to 7 March 2023 at the ARFF Unit at Adi Soemarmo Boyolali International Airport. Data collection techniques in this study used observation, interview, and documentation techniques and data analysis techniques used data reduction techniques, data presentation, and drawing conclusions. The results of the study show that the level of preparedness of the ARFF Unit at Adi Soemarmo Boyolali International Airport is increasing and continues to increase. The increase in the level of preparedness of the ARFF Unit was due to innovations and efforts issued by the airport so as to have an effect on the performance progress or preparedness of the ARFF unit at Adi Soemarmo Boyolali International Airport.